2021
DOI: 10.22146/bkm.63081
|View full text |Cite
|
Sign up to set email alerts
|

Preparing new normal: the health literacy assessment on the Covid-19

Abstract: Purpose: This study was aimed to assess the health literacy of the COVID-19 for both of the knowledge level on the Covid-19 and the health protocol compliance by the medical and the non-medical student. Method: This rapid action research was conducted from July-August 2020. Respondents were Indonesian students who voluntarily fulfilled the online questionnaire. A total 208 respondents participated in this study (104 students for each group). Data analysis was performed by using chi square. Furthermore, an anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The 'New Normal' strategy and policy led people to apply physical distancing. (5,12) It improved the opportunity of family member to have family time and spend more time to discuss and conduct activities together, including to discuss about COVID-19 as a disease with high morbidity and mortality. Families were able to stay connected and provide social support during pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 'New Normal' strategy and policy led people to apply physical distancing. (5,12) It improved the opportunity of family member to have family time and spend more time to discuss and conduct activities together, including to discuss about COVID-19 as a disease with high morbidity and mortality. Families were able to stay connected and provide social support during pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of awareness will lead to the poor health behavior on the COVID-19 prevention. 12 Unfortunately, research on family social capital is limited. 8 This current study aimed to describe the effect of family social capital on the COVID-19 prevention and examine determinants of the family social capital in the COVID-19 prevention in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…8 Therefore, health literacy becomes very important to practice a healthy lifestyle and health protocols to deal with COVID-19. 9 Health literacy is the ability of individuals or communities to access information, understand, and analyze health information with the ability to choose healthy life choices in their daily lives. 10 The high level of health literacy enables the community to participate in the healthy lifestyle movement GERMAS to prevent and control the spread of the COVID-19 virus.…”
Section: Introductionmentioning
confidence: 99%
“…However, the health literacy should be adjusted to the results of the assessment of community needs related to health literacy. 9 The condition of health literacy affects the use of information from professionals and experts. People with low levels of health literacy tend to use information and media with low levels of trust in information sources.…”
Section: Introductionmentioning
confidence: 99%
“…(23) Another study showed different results, in that medical students had better knowledge (41.8% vs 33.2%, p-value=0.000) and health protocol compliance (6.3% vs 2.4%, p-value=0.049) than non-medical students. (24) In a study conducted in Indonesia on the COVID-19 HL level of biology teacher candidate students, it was determined that most of the students did not have sufficient knowledge about COVID-19 symptoms, routes of transmission and the role of vaccines, and it was also suggested to provide these students with comprehensive education about COVID-19. (25) Similarly, in a study conducted on medical students, the relationship between the level of HL and fear of COVID-19 was investigated.…”
Section: Introductionmentioning
confidence: 99%